ANALISIS SUMBER DAYA DAN STANDAR KEBIJAKAN DALAM IMPLEMENTASI TATA RUANG KAWASAN PEMUKIMAN DI KECAMATAN PONTIANAK BARAT - Ibnureza Vairi E.01109033 (FISIP Universitas Tanjungpura, 2013)
This articlewas writtenbased on, the absencedecisive actionby theexecutivein implementingSpatial LayoutPolicyofResettlementAreain the districtin WestPontianak, whichcausesirregularonthe region, considering the position of thePlan SettlementRegionhas beenset aslocal regulationson thePontianakcitynumber04/2002. Aims of this article, to analyse the resources and standard an existing policy the implementation Spatial LayoutPolicyofResettlementAreain the districtof WestPontianak. Method of processing dataused in the writingthisarticleisa qualitativedescriptiveanalysis. The locationof thisresearchis in the Districtof WestPontianak. Research subjects are Head Office of Cipta Karya and Housing, Head Office of BAPPEDA Pontianak City, subdistrict head of West Pontianak. The resultsofthe writing ofthisarticleis, there are inadequate implementation of policiesin human resourcesin thedivision ofmonitoringandfinancial resources. As well,unclearthe contentsof thestandardpolicy make difficult fortheexecutivein implementingthe policy. Recommendationsofthe writing ofthisarticleis, toneed forimproving human resourcesin thefieldmonitoringdivisionandoperationalizeResidential Information Center, as well as makingDetailedSpatialPlan(RDTR)in order tosimplifythe executivein implementing the policy. Keywords : Residential Area, Human Resources and Financial, Detailed plans of settlement Space